2022
DOI: 10.1111/jcmm.17264
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species‐induced SIAH1 promotes granulosa cells' senescence in premature ovarian failure

Abstract: Premature ovarian failure (POF) is a common disease in women, characterized as abnormal declines in ovarian follicle numbers and oocyte quality. Patients have early depletion of primordial follicle pool associated with amenorrhea before the age of 40, which could be diagnosed by elevated serum FSH levels (>40 IU/L). 1,2 Causes of this disease could be mitochondrial dysfunction, auto-immune, chemotherapeutic treatments and cell senescence. 3 During ageing and senescence, accumulation of endogenous reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Excess germinal primordial follicles, inadequate development of follicles at all stages, and follicular pool depletion result in diminished ovarian reserve [ 3 ]. Previous studies have shown that its mechanism is mainly through oxidative stress damage, affecting hormone levels, and inducing germ cell apoptosis [ 5 ]. Based on the literature, we established a CTX-induced chemogenic POI rat model [ 21 ] and investigated the effect of preventative acupuncture on the Keap/Nrf2/HO-1 pathway in the pathogenic phase of POI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess germinal primordial follicles, inadequate development of follicles at all stages, and follicular pool depletion result in diminished ovarian reserve [ 3 ]. Previous studies have shown that its mechanism is mainly through oxidative stress damage, affecting hormone levels, and inducing germ cell apoptosis [ 5 ]. Based on the literature, we established a CTX-induced chemogenic POI rat model [ 21 ] and investigated the effect of preventative acupuncture on the Keap/Nrf2/HO-1 pathway in the pathogenic phase of POI.…”
Section: Discussionmentioning
confidence: 99%
“…During the therapeutic process, blood circulation abnormalities and related body stress injuries might cause a large amount of free radicals to be released. It promotes peroxidation and releases a substantial number of reactive oxygen species (ROS) which will damage the mitochondrial membrane and cell membrane of ovarian granulosa cells, induce an inflammatory cascade, release alarm signals (alarmins), and initiate a cellular response [ 5 ]. Granulosa cells in the ovary offer an important environment for the formation and development of egg cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Premature ovarian failure refers to a series of symptoms of perimenopausal hot flashes, night sweats, decreased libido, vaginal dryness, insomnia, reduced menstruation, sparse hair, even amenorrhea, and even infertility before the age of 40 due to the decline of ovarian function [ 1 , 2 ]. At the same time, it is accompanied by the decrease of estrogen, the increase of follicle stimulating hormone, and the increase or unchanged of luteinizing hormone [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was indicated by high SA-β-gal activity and ROS accumulation, along with the expression of the machinery for telomere shortening, which is upregulated by p53. 33 The relationship of cellular senescence with POI induced by gonadotoxic agents has been more thoroughly investigated than that with the idiopathic form. Various agents used in chemotherapy, including methotrexate, cisplatin, doxorubicin, and cyclophosphamide, have been reported to induce cellular senescence in the ovary.…”
Section: Primary Ovarian Insufficiencymentioning
confidence: 99%
“…Another study showed that GCs from patients with idiopathic POI have a senescent phenotype, unlike those from age‐matched controls. This was indicated by high SA‐β‐gal activity and ROS accumulation, along with the expression of the machinery for telomere shortening, which is upregulated by p53 33 …”
Section: Cellular Senescence In Pathological Conditions Of the Ovarymentioning
confidence: 99%